Multilayer Full Polarization Conversion Transpolarizing Structures - Misagh Khosronejad; Gian Guido Gentili; Giuseppe Macchiarella (International Journal of Antennas and Propagation)
In this paper, we propose the design of two perfect multilayered linear transpolarization structures working in transmission. These linear polarization converters are capable to rotate the polarization 90° independently from the direction of the input linear polarization. Results show an excellent conversion ratio.